Разложите на множители: 1)у^5-25у^3 2)16х+8х^2+х^3. Упростите выражение: 1)(х+7)^2-10х 2)(3а+p)(3a-p)+p^2. Решите уравнения: 1)(х^2-1)(х^2+3)=(х^2+1)^2+х.
Разложите на множители: 1)у^5-25у^3 2)16х+8х^2+х^3. Упростите выражение: 1)(х+7)^2-10х 2)(3а+p)(3a-p)+p^2. Решите уравнения: 1)(х^2-1)(х^2+3)=(х^2+1)^2+х.
Ответ(ы) на вопрос:
№ [latex]1[/latex] Разложить на множители
[latex]1)[/latex][latex]y^5 - 25y^3 = y^3 ( y^2 - 25)[/latex]
[latex]2)16x + 8x^2 + x^3 = x ( 16 + 8x + x^2)[/latex]
№[latex]2[/latex] Упростить выражение
[latex]1)[/latex][latex](x+7)^2-10x=[/latex][latex]( x + 7)( x + 7) - 10x = x^2 + 14x + 49 - 10x = x^2 - 4x + 49[/latex]
[latex]2)[/latex][latex]( 3a + p)( 3a - p) + p^2 = 9a^2 - p^2 + p^2 = 9a^2[/latex]
№[latex]3[/latex] Уравнение
[latex]( x^2 - 1)( x^2 + 3) = ( x^2 + 1)^2 + x[/latex]
[latex]x^4 + 3x^2 - x^2 - 3 = (x^2 + 1)(x^2 + 1) +x[/latex]
[latex]x^4 + 2x^2 - 3 = x^4 + 2x^2 + 1 + x[/latex]
[latex]x^4 + 2x^2 - 3 - x^4 - 2x^2 - 1 - x = 0[/latex]
[latex]- x - 4 = 0[/latex]
[latex]- x = 4[/latex]
[latex]x = - 4[/latex]
Не нашли ответ?
Похожие вопросы